Commentary on the New Testament use of the Old Testament - Beale, G. K. (Gregory K.) (Grand Rapids Baker Academic, 2007)
Readers of the New Testament often encounter quotes or allusions to Old Testament stories and prophecies that are unfamiliar or obscure. In order to fully understand the teachings of Jesus and his followers, it is important to understand the large body of Scripture that preceded and informed their thinking. Leading evangelical scholars G.K. Beale and D.A. Carson have brought together a distinguished team to provide readers with a comprehensive commentary on Old Testament quotations, allusions, and echoes that appear from Matthew through Revelation. College and seminary students, pastors, scholars, and interested lay readers will want to add this unique commentary to their reference libraries. - Publisher.
Keywords: Bible. -- New Testament -- Criticism, interpretation, etc. Bible. -- New Testament -- Relation to the Old Testament. Bible. -- N.T. -- Criticism, interpretation, etc. Bible. -- N.T. -- Relation to the Old Testament. Bible. -- New Testament. RELIGION -- Biblical Criticism & Interpretation -- New Testament. Neues Testament